Which Factors Influence on Mortality in Patients Undergoing Veno-Venous Extracorporeal Membrane Oxygenation (ECMO)? - Alireza jahangirifard; Mandana Hosseinzadeh; Sepideh Nazari; Amir Bahrami Ahmadi; Farhad Gorjipour; Seyed Bashir Mirtajani; Zargham Hossein Ahmadi (Archives of Anesthesia and Critical Care, 2022)
Background: There are inconclusive data of Ven venous extracorporeal membrane oxygenation (VV‐ECMO) VV‐ECMO for a therapeutic strategy for acute respiratory distress syndrome (ARDS). Methods: Totally 28 critically ill patients were included into the study between 23 September 2013 and 20 january 2020. Critically ill adult patients who were refractory to conventional therapeutic modalities were eligible for veno-venous ECMO and study inclusion. Results: Of a total of 28 patients, 15 patients (53.6%) survived and 13 (46.42%) died. Gender frequency had no significant difference between survivors and non-survivors (P=0.07). Mean of age and BMI had no significant differences between the mentioned groups also (P>0.05). It was the same for BSA and the two groups were in the same situation (1.82±0.37 vs. 1.79±0.29; P=0.81). There were no significant differences between survivors and non-survivors regarding ECMO time (114.49±91.05 vs. 162.62±100.17 minutes; P=0.20) and ICU stays (9.65±5.11 vs. 8.93±4.96; P=0.10). The average time of ICU stay was 9.29±5.16 days. The ejection fraction in survives was significantly higher than non-survivors (52.14±6.42 vs. 57.31±4.39; P=0.02). Those patients who were in the non-survivors group had lower blood pressure (MAP<65mmHg) during the study (P=0.049), however, did not find any significant differences between the groups regarding inotropes or vasoconstrictors. Conclusion: In this study, the mortality rate was 46.42%. Bleeding, hypotension and dialysis were the risk factors for mortality among study participants.